Occurrences of megabenthic organisms collected from Agassiz trawl catches taken in Canadian Arctic seas between 1953 and 1977 - Philippe Archambault; Mathieu Cusson; Jennifer Dannheim; Dieter Piepenburg (PANGAEA, 2024)
This dataset is a component of the PAN-Arctic data collection of benthic BIOtas (PANABIO) and has been collated during the Census of Marine Life project Arctic Ocean Diversity (ArcOD; http://www.arcodiv.org/). It contains a total of 2,435 presence records of 413 megabenthic taxa (species to genus level) identified in 110 Agassiz trawl catches taken at 110 stations located in various Canadian Arctic seas at water depths of 0–335 m during 18 cruises between 1953 and 1977. The dataset is also available in a PostgreSQL-based data warehouse that can be accessed and queried through an open-access frontend web service at https://critterbase.awi.de/panabio.
In: Piepenburg, Dieter; Brey, Thomas; Teschke, Katharina; Dannheim, Jennifer; Kloss, Paul; Hansen, Miriam Lea Sarah; Kraan, Casper (2023): PANABIO: A point-referenced pan-Arctic data collection of benthic biotas [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.963640